THE RELATIONSIP BETWEEN POPULATION AGES 30-34 AND INFLATION OF THE GROWTH DOMESTIC BRUTO INFLATOR - Irzameingindra Putri Radjamin; Almira Fidia Ramadhania; Patricia Evelyn Laksmana; Marcella Florentina Gunawan; Ridha Amallia Riadi; Shafira Ni'matul Istiqomah (Jurusan Ilmu Ekonomi Prodi Ekonomi Pembangunan Fakultas Bisnis dan Ekonomika Universitas Surabaya, 2022)
This study aims to determine the relationship between the population aged 30-34 years and inflation as measured by the Gross Domestic Product (GDP) deflator. The method used in this study is the Granger Causality Test. The impact of this research can be seen from this study's results, which is men aged 30-34 years are very influential in the economy. Moreover, most workers in this world are men. The population aged 30-34 greatly influences economic growth and inflation. The male population aged 30-34 has more influence on economic growth and inflation than the female population aged 30-34. In the opposite direction, an increase in unemployment causes GDP to grow more slowly or even fall. Labor is one of the factors driving GDP growth. Increased population growth also has a positive effect on government spending. However, the inflation rate will also have a negative impact on government spending. A high inflation rate can worsen the value of a country's real GDP. If GDP increases, then a country's economic growth is improving. And if the average rate of economic growth in a country from year to year is higher, the income per capita of the community will also increase.